(untitled) (Neo Science Peer Reviewed Journal, 2023)
The report is devoted to the approaches of the Republic of Uzbekistan to resolving issues related to security and development in Afghanistan. In addition, a retrospective analysis of the efforts of the Republic of Uzbekistan aimed at achieving peace and stability in Afghanistan is carried out.